Association between nanoscale strains and tissue level nanoindentation properties in age-related hip-fractures - Bonicelli, Andrea; Tay, Tabitha; Cobb, Justin P.; Boughton, Oliver R.; Hansen, Ulrich (Elsevier, 2023)
Measurement of the properties of bone as a material can happen in various length scales in its hierarchical and composite structure. The aim of this study was to test the tissue level properties of clinically-relevant human bone samples which were collected from donors belonging to three groups: ageing donors who suffered no fractures (Control); untreated fracture patients (Fx-Untreated) and patient who experienced hip fracture despite being treated with bisphosphonates (Fx-BisTreated). Tissue level properties were assessed by (a) nanoindentation and (b) synchrotron tensile tests (STT) where strains were measured at the ‘tissue’, ‘fibril’ and ‘mineral’ levels by using simultaneous Wide-angle - (WAXD) and Small angle- X-ray diffraction (SAXD). The composition was analysed by thermogravimetric analysis and material level endo- and exo-thermic reactions by differential scanning calorimetry (TGA/DSC3+). Irrespective of treatment fracture donors exhibited significantly lower tissue, fibril and mineral strain at the micro and nanoscale respectively and had a higher mineral content than controls. In nanoindentation only nanohardness was significantly greater for Controls and Fx-BisTreated versus Fx-Untreated. The other nanoindentation parameters did not vary significantly across the three groups. There was a highly significant positive correlation (p < 0.001) between organic content and tissue level strain behaviour. Overall hip-fractures were associated with lower STT nanostrains and it was behaviour measured by STT which proved to be a more effective approach for predicting fracture risk because evidently it was able to demonstrate the mechanical deficit for the bone tissue of the donors who had experienced fractures.
Keywords: Bone properties; Synchrotron; Nanoindentation; Fracture; Ageing